Application of a two-dimensional gas chromatography for analysis of lard and other fats and oils - Indrasti, Dias (2010)
Lard is an important ingredient in the food industry because of its physical and chemical properties as well as its economic importance. However, the utilization and consumption of lard and other porcine-based products are strictly forbidden for followers of certain religions, especially Islam. In order to protect the interest of the Muslim consumers, it is important to develop a novel method to ascertain the absence of lard in foods. For this reason, the study on analysis of fatty acids (FA), mono- and diacylglycerols (MG-DG) of lard and other fats and oils for halal authentication was conducted. FA structure and composition in fats and oils would give specific character and could be used as an indicator for determination of the lipid source. Using comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry (GC×GC-TOF-MS) method, analysis of fatty acids involves conversion of fatty acids to methyl ester components. Chromatogram of FA profile of animal fats such as lard (LA), chicken fat (CF), cattle fat (CA) and goat fat (GF), showed that methyl hexadecanoate (C16:0), methyl trans-9-octadecenoate (C18:1 n9t) and methyl octadecanoate (C18:0) were the most abundant peaks. However, a few components were observed to be high in the specific sample such as C18:2 n6t in LA and CF, C14:0 in CA and C18:1 n9c in GF. GF also contained various and significant amounts of branched chain FA such as C13:0ai, C14:0ai, C15:0i, C15:0ai, C16:0i, C17:0i, C17:0ai, C18:0i, C19:0i and C19:0ai. LA could conveniently be differentiated from other animal fats by the presence of FA such as methyl trans-9,12,15-octadecatrienoate (C18:3 n3t), methyl 11,14,17-eicosatrienoate (C20:3 n3t) and methyl 11,14-eicosadienoate (C20:2 n6). Characterization of MG-DG in fats and oils could be important criteria in determining the source of origin of a particular lipid. The GC×GC-TOF-MS technique incorporated with a fast GC microbore column was demonstrated to rapidly unravel the composition of MG-DG in the products of the glycerolysis process from five different fats/oils including palm oil (PA),lard (LA), sunflower seed oil (SF), corn oil (CO) and butter (BU). LA and PA profile relatively covered wide-range of MG-DG, from short-chain to long-chain carbon atoms in their glycerol backbone. SF contained long-chain MG-DG, in contrast with BU which only has short-chain MG-DG. SF has only few types of MG-DG, which were palmitic acid in the sn-3 position and stearic acid for MG, while C18:1t and C18:2c for DG. SF did not have any short-chain fatty acid in the glycerol backbone. SF and CO only contained C16:0 and C18:0 in their MG groups. CO comprised of long-chain fatty acids in its DG profile. C18:1t and C18:2c were the main DG groups present in SF. In conclusion, this study provides a rapid method to characterize FA and regiospecific isomers of MG-DG from lard and selected fats/oils using GC×GC-TOF-MS technique.